A New Porous Hybrid Material Derived From Silica Fume and Alginate for Sustainable Pollutants Reduction - Zanoletti, Alessandra; Vassura, Ivano; Venturini, Elisa; Monai, Matteo; Montini, Tiziano; Federici, Stefania; Zacco, Annalisa; Treccani, Laura; Bontempi, Elza (Frontiers in Chemistry, 2018)
In this work a new mesoporous adsorbent material obtained from a natural, high abundant raw material and a high volume industrial by-product is presented. The material is consolidated by the gelling properties of alginate and by decomposition of sodium-bicarbonate controlled porosity at low temperatures (70-80°C) at different scale lengths. The structural, thermal, and morphological characterization shows that the material is a mesoporous organic-inorganic hybrid. The material is tested as adsorbent, showing high performances. Methylene blue, used as model pollutant, can be adsorbed and removed from aqueous solutions even at a high concentration with efficiency up to 94%. By coating the material with a 100 nm thin film of titania, good photodegradation performance (more than 20%) can be imparted. Based on embodied energy and carbon footprint of its primary production, the sustainability of the new obtained material is evaluated and quantified in respect to activated carbon as well. It is shown that the new proposed material has an embodied energy lower than one order of magnitude in respect to the one of activated carbon, which represents the gold standards. The versatility of the new material is also demonstrated in terms of its design and manufacturing possibilities. In addition, this material can be printed in 3D. Finally, preliminary results about its ability to capture diesel exhaust particulate matter are reported. The sample exposed to diesel contains a large amount of carbon in its surface. At the best of our knowledge this is the first time that hybrid porous materials are proposed as a new class of sustainable materials, produced to reduce pollutants in the wastewaters and in the atmosphere.